Alliances or Acquisition? An Examination of Strategic Decisions of Lenovo and TCL in Developed Market - Liu, Yang (2012)
Abstract Internationalisation has become the major topic for both scholars and practitioners in recent years. Different with the business conditions in the previous decades, MNEs from the developing nations have become major power of outward FDI activities. Over the years of development, China has not only been regarded as the most attracting FDI inward place for foreign investors, but also it has become the important player in the FDI outward activities. Theoretically, a great number of studies have been conducted to identify the motives behind the FDI outward activities of MNEs from emerging markets such as China. As majority of emerging MNEs use acquisitions or strategic alliances with the well-established brands in the developed markets, the aim of this study is to explore the key determinants for the entry mode choices between the alliances and the acquisition. To this end, this study conducts the case study of two successful Chinese international brands, the Lenovo and the TCL, with a focus on their entry mode strategy in the US and the European market. The study identifies eight factors that greatly affect the choices between the acquisition and the alliances for these two case companies. Under such conditions, the best suitable entry mode choices for the emerging MNEs seems to be determined by the intangible assets, the industrial similarities between China and the target host country, the industrial growth, the transaction cost, partner size, company's international experience, capital intensity, the market size and preference. The study shows that the choice of between alliances and acquisition is shaped by multiple factors.